1994
DOI: 10.1111/j.1460-9568.1994.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Axonal Transport of the α‐Subunit of the GTP‐binding Protein Gz in Mouse Sciatic Nerve: a Potential Pathway for Signal Transduction In Neurons

Abstract: We have utilized antibodies against the alpha subunit of GZ in fluorescence immunohistochemistry to determine whether this GTP-binding protein can translocate along nerves by intra-axonal transport. After ligation of the mouse sciatic nerve we found an increase in GZ-like immunoreactivity on the proximal and distal side with time, suggesting that the alpha subunit undergoes orthograde axonal transport and also returns to the cell body by retrograde axonal transport in the sciatic nerve. Unlike the retrograde t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Our studies have identified one possible organelle that may convey the NGF signal down axons. Important signaling events may be mediated through TrkA in other organelles, through p75 NTR , or through signal transduction mediators downstream from receptors (45). Because it was the first NGF receptor to be discovered, p75 NTR was invoked in earlier versions of the ''signaling vesicle'' hypothesis (1,2).…”
Section: Resultsmentioning
confidence: 99%
“…Our studies have identified one possible organelle that may convey the NGF signal down axons. Important signaling events may be mediated through TrkA in other organelles, through p75 NTR , or through signal transduction mediators downstream from receptors (45). Because it was the first NGF receptor to be discovered, p75 NTR was invoked in earlier versions of the ''signaling vesicle'' hypothesis (1,2).…”
Section: Resultsmentioning
confidence: 99%
“…However, Crouch et al (1994) suggested that the Gz protein is related to the signal transduction of neurotrophins, and Hendry et al (2000) recently reported that Gαz-deficient mice showed high tolerance to morphine in comparison to wild-type mice. The presence of Gz proteins in MCs may be related to the regulation of mechanoreceptive actions of the cells.…”
Section: A-e ×350mentioning
confidence: 97%
“…Positive immunodetection of · z in dorsal root ganglion strongly supports the unique role of · z in sensory neurons [63]. Both orthograde and retrograde axonal transports of · z have been detected through ligation experiments using sensory sural nerve, sciatic nerve and dorsal root ganglion [59,63]. The retrograde axonal transport of · z targets to the nuclei of the neurons [64,65], which implies the retrograde signals carried by · z may have nuclear functions.…”
Section: Signaling Function Of G Zmentioning
confidence: 85%
“…It is generally accepted that signaling events occurring at the synaptic end of an axon can be transmitted back to the cell body and the nucleus through retrograde axonal transport of signaling complexes. Trimeric G proteins (e.g., G i [58] and G z [59]), components of the MAP kinase cascade [60], neutrotrophic factors and their receptors [61,62] are all transported along the axons. The axonal tranport of · z is found in sciatic axons, which is distinct from the distribution of G i proteins [59].…”
Section: Signaling Function Of G Zmentioning
confidence: 99%
See 1 more Smart Citation